Reproductive features and gametogenesis of Dendrophyllia ramea from the Alboran Sea, Western Mediterranean - Orejas, Covadonga; Antón-Sempere, Silvia; Terrón-Singler, Alexis; Grau, Amalia (PANGAEA, 2023)
This bundled publication contains data sets on 1) Polyp size and sex: biometric data of polyps from Dendrophyllia ramea, as well as the sex of each analysed polyp; 2) Oocyte per mesentery: number of oocytes per analysed mesentery; 3) Oocytes per polyp: these data have been used to calculate fecundity; 4) Oocyte developmental stages: oocyte sizes and developmental stage are included; 5. Spermatic cysts: spermatic cysts sizes and developmental stage are included. A total of three polyps per each coral colony have been analysed by histological methods and a total of three coral colonies have been analysed for each sampling month: February 2018, May 2017, July 2018 and October 2017. Samples have been collected in the protected area of Punta La Mona (Granada, Alborán Sea, western Mediterranean) between 30 and 37 meters depth by scuba diving.
Keywords: Alboran Sea; cold-water corals; Dendrophyllia ramea; gametogenesis; Reproduction; Western Mediterranean Sea